Studi Pemanfaatan Dermaga Dalam Menunjang Aktifitas Bongkar Muat Dan Tambat Labuh Kapal Perikanan Di Pangkalan Pendaratan Ikan (PPI) Klaligi Kota Sorong - Melani Manurung; Clara Payung; Jhonly (INTEGRATED OF FISHERIES SCIENCE, 2022)
The purpose of this research is to be able to describe the condition of the PPI Klaligi pier in Sorong City, to determine the level of stakeholder satisfaction in utilizing the PPI pier. The method used in street vendors is quantitative descriptive, namely through direct observation/observation, interviews, filling out questionnaires and literature study. Based on the research results, the condition of the PPI wharf is currently in good condition, the level of stakeholder satisfaction with jetty dock services and facilities is as follows: Loading and unloading: 73% of stakeholders are satisfied with the level of loading and unloading services at PPI Klaligi wharf. Mooring: 80% of stakeholders are satisfied with the level of mooring service at PPI. Physical condition: 73% of stakeholders are quite satisfied with the physical condition of the PPI pier. Capacity: 80% of stakeholders are dissatisfied with the capacity and size of the PPI Klaligi pier.